Net neutral carbon responses to warming and grazing in alpine grassland ecosystems - Lv, Wangwang; Luo, Caiyun; Zhang, Lirong; Niu, Haishan; Zhang, Zhenhua; Wang, Shiping; Wang, Yanfen; Jiang, Lili; Wang, Yonghui; He, Jinsheng; Kardol, Paul; Wang, Qi; et al. (Agricultural and forest meteorology, 2020)
•Warming did not alter annual total ecosystem CO2 exchange (annual NEE).•Summer grazing decreased a net carbon sink, but winter grazing increased it.•Interactions between warming and grazing on NEE varied with year and grazing season.•Rotational grazing between summer and winter seasons caused neutral climate feedback. In natural grasslands, effects of warming on net ecosystem CO2 exchange (NEE) may interact with grazing. Yet, the effects of these two main drivers of terrestrial carbon cycling are typically studied in isolation, limiting our understanding of how NEE would be affected under different global change scenarios. Here, we report results of a warming experiment using infrared heaters combined with summer and winter grazing for 7-years in a Tibetan alpine grassland. We found that regardless of warming summer grazing decreased soil carbon sink (i.e., increased annual mean net biome productivity (NBP) indicated by a negative value of NBP), and warming also reduced soil carbon sink under no-grazing only during 3-years of summer grazing. However, warming and grazing did not change soil carbon sink during 4-years of winter grazing. Interactive effects between warming and grazing on annual NBP varied with year and grazing season. Overall, both warming and grazing did not alter annual mean NBP under 7-years of the rotational grazing system in summer and winter grasslands because of offsetting effects on annual mean gross primary productivity and ecosystem respiration. Annual mean soil temperature explained 58% of the variation of annual mean NBP during summer grazing, whereas seasonal mean soil moisture explained 48 and 44% of its variation during winter grazing and the two season grazing system, respectively. Together, our results suggest that rotational grazing between summer and winter alpine grasslands would result in net neutral climate feedback based on the response of annual NBP under future warming. The two season grazing system not only supports animal production but also realizes balance in the soil carbon budget under future warming.